Impact of a game-based tool on student engagement in a foreign language course: a three-term analysis - Anane, Chiraz (Frontiers in Education, 2024)
In recent years, the use of game-based learning platforms has gained significant attention in educational settings for their potential to enhance student engagement and learning outcomes. This paper examines the effectiveness of Kahoot!, a game-based student response system, in an online French as a foreign language course. The study aims to assess how students perceive Kahoot! across three academic terms. A mixed-methods approach was used, combining quantitative data from structured questionnaires with qualitative insights from open-ended questions. This provided a comprehensive view of student perceptions and experiences with Kahoot!. The findings show consistently high student enthusiasm and engagement with Kahoot! across the three terms. Most students strongly agreed that Kahoot! positively impacted their learning, with high mean scores and low standard deviations reflecting widespread consensus. However, some students showed variations in competitive motivation, and minor technical challenges were noted. Overall, the study underscores Kahoot!’s sustained effectiveness in improving student engagement and learning in online French courses. Despite variations in motivation and some technical issues, the tool was largely seen as beneficial. This research adds to the growing evidence of the value of game-based learning tools in online education, particularly for foreign language instruction.